The saga and limits of public financial management: The Mozambican case - António Cruz; Ines A. Ferreira; Johnny Flentø; Finn Tarp; Mariam Umarji (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
At independence in 1975, the Frelimo government took over public administration from the colonial system and started to transform it. The public financial management (PFM) system was adapted to the central planning and management of the economy in line with nationalist and Marxist-Leninist thinking. Collapse followed in the mid-1980s, amidst the Cold War and the liberalization of the economy. The PFM system was gradually and systematically reformed towards more transparent and efficient mechanisms, and successful reforms did coincide with high rates of economic growth for more than 20 years, after 1993. The reform process was supported by sizeable foreign aid to the extent that Mozambique became highly aid dependent. As the nationalist agenda became more forceful from around 2005-10, when the existence of large natural gas reserves in the Rovuma Basin was confirmed, the extraction of natural resources became the main government focus as a source of public revenue, and severe cracks in the PFM system started to emerge. The 'hidden debt' scandal in 2013-14, the renewed conflict between Frelimo and Renamo from 2013, and the insurgency war in Cabo Delgado from 2017 put the PFM system under pressure and performance suffered accordingly with significant economic and social costs. The paper brings out how difficult it is to make institutional reforms work, within a structure of political and economic power that may not benefit from them, even in the context of a high degree of aid dependence.
Keywords: H50; H60; O43; P51; 330; public financial management; Mozambique; reforms; general budget support